The ANALYSIS OF WARNING LETTER AND DISTRESS WARRANT AGAINST THE DISBURSEMENT OF TAX ARREARS AT THE NORTH JAKARTA MIDDLE TAX OFFICE - Dinar Riftiasari; Sugiarti Sugiarti (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
Tax collection in increasing tax revenue can be through warning letter and distress warrant. This study is to analyze the warning letter and distress warrant as independent variables on the disbursement of tax arrears as a dependent variable at the north jakarta middle tax office. This research uses quantitative methods by using analysis techniques of correlation coefficient testing, test the coefficient of determination, and multiple linear regression. The research data were sourced from secondary data of north jakarta middle tax office period 2013 to 2017. The results of the analysis of the correlation coefficient test showed that partially or simultaneously correlations between warning letter and distress warrant against disbursement of tax arrears there was no significant relationship. The coefficient of determination test shows that simultaneous warning letter and distress warrant do not affect the disbursement of tax arrears. The equation of the multiple regression results of this study is Y = 12807695261.8 - 8297820.152 X1 - 52620266.169 X2.